A study on the determination of handgrip strength of Olympic style weightlifting athletes - Kenan Erdağı; Osman Tüfekçi; Mustafa Yeşeri; Mehmet F. Yüksel; Nimet Turgut; Burak E. Eroğlu (Physical Education of Students)
Background and Study Aim: Handgrip strength is widely accepted as a functionality parameter to assess upper extremity performance. The measurement of hand grip strength by dynamometry is a low cost, non-invasive method of simple applicability. The present study is based on the association of dominant and non-dominant handgrip strength with demographic and anthropometric characteristics; height, body weight, body mass index, upper arm length, forearm length, hand length, forearm circumference, upper arm circumference.